Study of mode of delivery and fetal outcome in pregnancies with oligohydramnios - B., Lavanya; Prajwala, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The significance of amniotic fluid volume as a marker of fetal status is an ongoing turn of events. Oligohydramnios causes adverse fetal outcomes like meconium-stained liquor, meconium aspiration syndrome, fetal heart rate abnormalities, poor APGAR scores, fetal growth restriction and fetal prematurity. It is associated with maternal hypertension, infections, and placental insufficiency. It causes maternal complication because of increased incidence of induction of labour and operative intervention. Methods: Hundred cases of oligohydramnios were included in our study conducted at the Navodaya medical research, hospital and research centre, during a period of two years after obtaining the informed consent of patients and institutional ethical clearance. All gravidas were included with a gestational age greater than 28 weeks with singleton pregnancies with oligohydramnios. Associated fetal and maternal risk factors were observed. The amniotic fluid index (AFI) was measured by ultrasound. The nonstress test, the fetal biophysical profile and the Doppler study were carried out to evaluate the fetal condition. Then we have observed for delivery and fetal outcome. Results: Incidence of oligohydramnios was 2.85% in our study. The 53% of cases had LSCS while 47% had normal delivery. Fetal distress was the commonest indication for LSCS. Poor neonatal APGAR score was 16.9% in LSCS while 36% in vaginal delivery. Conclusions: From the above study, the caesarean delivery seems to be a safer mode of delivery than vaginal delivery because it is associated with a good perinatal outcome.